Elemental analysis of aerosols collected at the Pierre Auger Cosmic Ray Observatory with PIXE technique complemented with SEM/EDX - Micheletti, Maria Isabel (2012)
The aim of this work is to characterize surface aerosols at the Pierre Auger Cosmic Ray Observatory located at Pampa Amarilla, near Malargüe city, in the Andes region of Argentina, with experimental sampling techniques used for the first time in a cosmic ray observatory, adding to information provided by the existing Auger aerosol monitors. A good knowledge of the optical attenuation due to aerosols is crucial for a good reconstruction of the signals from cosmic ray showers detected by the fluorescence detectors of the Observatory. Aerosols were collected in filters, during the Southern Hemisphere winter and spring in 2008. Concentrations in PM2.5 and PM2.5?10 filters were determined by gravimetric analysis and their elemental composition by the PIXE technique, complemented with SEM/EDX. Low aerosol concentrations were measured during the sampling period. The mean total mass PM10 (=PM2.5 + PM2.5?10 fractions) value was [mean(se)] 9.8(1.0) lg/m3 [sd = 5.9 lg/m3]. The mean PM10 value during winter was 7(1.1) lg/m3 [sd = 4.5 lg/m3], about half of the 13.1(1.5) [sd = 5.7 lg/m3] measured during springtime. The PM2.5 fraction was approximately 30% of the PM10 fraction. PIXE results gave levels of S, Cl, K, Ca, Ti, Mn, Fe in the analyzed aerosol samples, showing that these elements correspond to 25% and 13% of the PM2.5 and PM2.5?10 total mass respectively. The rest of the mass was due to the elements with low Z (below 16) which cannot be detected by our X-ray setup. Comparison with SEM/EDX analysis showed that most of them were Si and Al (aluminosilicates). Our results indicate that most of the aerosols at the Auger Observatory would most likely come from the soil of the region. Due to its vast atmospheric monitoring network, the Auger Observatory is an interesting reference site for further atmospheric studies.